A Battery Made from a Single Material. (30th April 2015) - Han, Fudong; Gao, Tao; Zhu, Yujie; Gaskell, Karen J.; Wang, Chunsheng
<x xml:space="preserve">Abstract</x> A single‐material battery is prepared using Li10GeP2S12 as the electrolyte, anode, and cathode, based on the Li–S and Ge–S components in Li10GeP2S12 acting as the active centers for its cathode and anode performance, respectively. The single‐Li10GeP2S12 battery exhibits a remarkably low interfacial resistance due to the improvement of interfacial contact and interactions, and the suppression of interfacial strain/stress.